A novel soft sensor approach for estimating individual biomass in mixed cultures. (20th March 2017) - Stone, Kyle A.; Shah, Devarshi; Kim, Min Hea; Roberts, Nathan R. M.; He, Q. Peter; Wang, Jin
Abstract : Due to many advantages associated with mixed cultures, their application in biotechnology has expanded rapidly in recent years. At the same time, many challenges remain for effective mixed culture applications. One obstacle is how to efficiently and accurately monitor the individual cell populations. Current approaches on individual cell mass quantification are suitable for off‐line, infrequent characterization. In this study, we propose a fast and accurate "soft sensor" approach for estimating individual cell concentrations in mixed cultures. The proposed approach utilizes optical density scanning spectrum of a mixed culture sample measured by a spectrophotometer over a range of wavelengths. A multivariate linear regression method, partial least squares or PLS, is applied to correlate individual cell concentrations to the spectrum. Three experimental case studies are used to examine the performance of the proposed soft sensor approach. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:347–354, 2017